Pemberdayaan Remaja Panti Asuhan Putri Muhammadiyah Purwokerto Tentang Kosmetik Aman dan Halal Menggunakan Metode Game Teaching - Much Ilham Novalisa Aji Wibowo; Githa Fungie Galistiani (Universitas Mathla'ul Anwar Banten, 2018)
EMPOWERMENT OF YOUTH PUTRI MUHAMMADIYAH PURWOKERTO ORPHANAGE ABOUT SAFE AND HALAL COSMETICS USING THE GAME TEACHING METHOD. Cosmetics are a necessity that has an important role in the field of beauty for the beauty of the human body. LPPOM MUI said that the use of cosmetic ingredients should contain safe and halal material. Survey says that 6 out of 10 teenage girls orphanage muhammadiyah purwokerto that were used in cosmetics, assume that only halal cosmetics logo already been guaranteed safety and halal. The measurement results of pre-test knowledge of halal cosmetics is in a category of knowledge is low (<56%). The solution provided is to empower young women by increasing knowledge relating to cosmetic. The method used is lectures that are packed with game teaching. The result of this activity looks at feedback is shown by the partners of the questions and answers appear when teaching the game in progress. The level of knowledge is measured by a questionnaire instrument compiled from a safe and halal method of choosing cosmetics. Questionnaires were compiled as many as 20 questions which fulfilled 3 aspects of knowledge namely knowing, understanding and applying. The majority of participants have increased knowledge of the low knowledge category into a midle category by the number of questions answered correctly ranged from 56%-75%.